Fock representation of the binary shift algebra - Vik, Sigmund (MATHEMATICA SCANDINAVICA, 2001)
We modify the Fock representation construction of the CAR-algebra to obtain a new proof for that the Binary Shift Algebra is isomorphic to the CAR-algebra.